BLENDED LEARNING : SUATU TINJAUAN PERSPEKTIF DUNIA PENDIDIKAN DAN PELATIHAN - FARHAT, M.; NOVARIA, EVA; SUTALHIS, SUTALHIS; YUSUF, A. (CENDEKIA: Jurnal Ilmu Pengetahuan, 2024)
Blended learning system, is a solution to the problems of education and training faced by various training institutions both organized by government and private education and training institutions. In Government training education institutions known as LMS is able to overcome various problems of cost, time, place and distance. Research using observations on the implementation of PKA Training activities, PKP South Sumatra Province in 2024, Publish or Perish searches by searching 500 publications from 2020 to 2024, filtered 392 publications originating from journals, then visualized with the VOS viewer application. The implementation of the Blended Learning System requires (1) Careful planning, curriculum design, including the selection of online platforms, preparation of materials, and schedules for face-to-face sessions (2) Training for Facilitators: Facilitators should be trained to manage online and face-to-face learning effectively. They should also be able to use e-learning technology well, (3) Technology Support: ensuring all participants have adequate access to technology devices and internet, (4): Evaluation/feedback and (5) Innovative and flexible approaches to managerial training. ABSTRAKBlended learning System, merupakan suatu solusi atas permasalahan pendidikan dan pelatihan yang dihadapi berbagai lembaga Pelatihan baik yang diselenggarakan oleh lembaga Pendidikan dan pelatihan Pemerintah maupun swasta. Pada lembaga Pendidikan pelatihan Pemerintah ynag dikenal dengan LMS mampu mengatasi berbagai persoalan biaya, waktu, tempat dan jarak. Penelitian menggunakan pengamatan pada pelaksanaan kegiatan Pelatihan PKA, PKP Provinsi Sumatera Selatan Tahun 2024, penelusuran Publish or Perish dengan penelusuran 500 publikasi dari tahun 2020 sampai dengan 2024, tersaring 392 publikasi yang berasal dari jurnal, kemudian dilakukan visualisasi dengan aplikasi VOS viewer. Pada pelaksanaan Blended Learning System membutuhkan (1) Perencanaan yang matang, desain kurikulum, termasuk pemilihan platform online, penyusunan materi, dan jadwal sesi tatap muka (2) Pelatihan untuk Fasilitator : Fasilitator harus dilatih untuk mengelola pembelajaran online dan tatap muka secara efektif. Mereka juga harus mampu menggunakan teknologi e-learning dengan baik, (3) Dukungan Teknologi: memastikan semua peserta memiliki akses yang memadai ke perangkat teknologi dan internet , (4) : Evaluasi /umpabn balik dan (5) Pendekatan inovatif dan fleksibel untuk pelatihan manajerial.